Pengaruh Efektifitas Pemberlakuan PSBB Terhadap Produktivitas Masyarakat di Daerah Jakarta Pusat - Tomi Kristian; Loeky Rono Pradopo; Andyan Pradipta Utama (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The Effect of the Effectiveness of the Implementation of PSBB in Central Jakarta on Community Productivity. This research was conducted to see the effectiveness of PSBB implementation on the productivity of the people of Central Jakarta. The variables studied were the effectiveness variable (X) and the productivity variable (Y). This type of research is descriptive quantitative. The data collection technique used was a questionnaire. Furthermore, the sampling technique used was purposive sampling technique with 100 respondents. The results showed that effectiveness had an effect on the productivity of the people of Central Jakarta. Based on this, it is recommended that all the general public and especially Central Jakarta should increase their knowledge about COVID-19 and how to prevent it, so that daily activities are safer and positive numbers can be minimized and remain productive even during the PSBB period